The Rise of Digital Responsibility: Insights From Türkiye's Banking and E-Commerce Sectors - Aydogdu, Ceyda Cihan; Karsak, Banu Mujde Baskan; Baskan Karsak, Banu Mujde; Cihan Aydogdu, Ceyda (Wiley, 2025)
This study examines how the concept of corporate digital responsibility (CDR) principles, such as data security, transparency, and digital inclusivity, is integrated into the corporate structures of the banking and e-commerce sectors in T & uuml;rkiye. The objective is to identify sector-specific key trends, challenges, and strategic approaches related to the adoption of CDR in corporate frameworks. By presenting a comparative analysis of two critical sectors, this research highlights the sectoral differences in understanding and implementing CDR. Employing a qualitative methodology, the research utilizes semi-structured interviews with senior executives, corporate communication directors, IT professionals, and legal experts. The interviews were thematically analyzed and digitized using Python-based coding tools to enhance analytical consistency and depth. The findings indicate that the banking sector demonstrates greater maturity in CDR awareness and an institutionalized approach to CDR, particularly in areas related to data security and regulatory compliance. Conversely, the e-commerce sector shows slower and more fragmented progress, lagging in the adoption and implementation of CDR principles. Both sectors require significant improvements to align with global CDR standards. The study also underlines the importance of cross-sector collaboration, government enforcement mechanisms, and user-driven demands in fostering responsible digital ecosystems. Future studies should employ quantitative methods to evaluate the regulatory and cultural influences on digital responsibility. Furthermore, research that focuses on consumer perspectives, the long-term development of regulatory compliance, and compares different emerging economies will help broaden the current literature on CDR.
Keywords: Corporate Digital Responsibility; Corporate Social Responsibility; Digital Transformation